Influence of Leadership, Intellectual Ability, and Work Environment on Employee Performance - Mate, Christina (Journal of Business Management and Economic Development, 2023)
The study tested the variables of leadership, intellectual ability, and work environment on employee performance at the Tanah Jawa District Office, Simalungun Regency, North Sumatra, with a total of 32 employees. This research uses quantitative and qualitative methods. The results showed that the questionnaire data instrument items were stated to be valid and reliable. The regression equation produces a positive correlation between leadership, intellectual ability, and work environment variables on employee performance with work environment variables having the greatest relationship to employee performance. Partially (the t-test) shows that leadership has a significant effect on employee performance, intellectual ability has a significant effect on employee performance, and work environment has a significant effect on employee performance. Simultaneously the variables of leadership, intellectual ability, and work environment have a positive and significant effect on performance. This shows that leadership, intellectual ability, and work environment if they work well in an organization and can become a support for employees will have a positive impact on employee performance.